Predictors and Timing of Hypotension and Bradycardia after Carotid Artery Stenting - Lavoie, P.; Rutledge, J.; Dawoud, M.A.; Mazumdar, M.; Riina, H.; Gobin, Y.P. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Hypotension and bradycardia are common in carotid artery stenting (CAS) and are particularly worrisome in the high risk patient who is typically referred for CAS. The purpose of this work was to assess the incidence and predictors of hypotension and bradycardia and the risk of their delayed occurrence after CAS.MATERIALS AND METHODS: A total of 53 men and 40 women (median age, 71 years) with symptomatic (57%) or asymptomatic (42%) carotid artery stenosis had CAS performed in our institution between December 2002 and January 2007. Patient vital sign records for the 12 hours post-CAS were analyzed. The relative decrease of blood pressure and pulse rate were used as primary end points, and the requirement of pressor or anticholinergic drugs was used as a surrogate end point. Significant predictors of hypotension and bradycardia were analyzed with a logistic regression model. Cumulative freedom from hypotension and bradycardia was calculated by using the Kaplan-Meier method. Negative predictive value (NPV) of screening for early hypotension and bradycardia was determined.RESULTS: The incidence of hypotension, bradycardia, and both was 14%, 23%, and 15%, respectively. Drug intervention was required in 45 patients (48%). Asymptomatic stenosis was an independent predictor of hypotension and bradycardia. Stenosis proximity to the bifurcation and dilation percentage were independent predictors of the drug intervention requirement. Seven patients (8%) had new onset of hypotension or bradycardia later than 6 hours post-CAS. The NPV of early hypotension and bradycardia was 97% and 93%, respectively.CONCLUSION: In this retrospective study, the risk of hypotension or bradycardia after CAS is significantly influenced by the degree of dilation performed, and the risk of their delayed occurrence may justify a minimum of 12 hours postprocedural vital sign monitoring.